2022
DOI: 10.1177/03057356221135355
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relations between Big Five personality traits and musical emotions embodied in spontaneous dance

Abstract: We explored the hypothesis that musical emotions are embodied differentially by people according to their personality. Nine hundred and fifty two individuals completed the Big Five personality inventory. A subset of 60 participants were asked to spontaneously move to 30 short musical stimuli while being recorded with a motion-capture system. The musical stimuli were separately rated for perceived emotions. Embodied musical emotions were evaluated as the correlation between features derived from the motion-capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…For example, the five-factor model of personality (Digman, 1990;McCrae & John, 1992), that includes social-related factors such as extraversion, agreeableness, or openness, have been reported to positively correlate with ensemble aptitude (Kawase, 2016). Studies on spontaneous movement to music have also found links between these personality factors and how musical emotions are embodied (Mendoza Garay et al, 2023), as well as with their responsiveness to small tempo changes (Carlson et al, 2016).…”
Section: Personality-related Social Factorsmentioning
confidence: 99%
“…For example, the five-factor model of personality (Digman, 1990;McCrae & John, 1992), that includes social-related factors such as extraversion, agreeableness, or openness, have been reported to positively correlate with ensemble aptitude (Kawase, 2016). Studies on spontaneous movement to music have also found links between these personality factors and how musical emotions are embodied (Mendoza Garay et al, 2023), as well as with their responsiveness to small tempo changes (Carlson et al, 2016).…”
Section: Personality-related Social Factorsmentioning
confidence: 99%